The binary locating-dominating number of some convex polytopes - Simić, Ana (Ars mathematica contemporanea, 2017)
In this paper the binary locating-dominating number of convex polytopes is considered. The exact value is determined and proved for convex polytopes ?$D_n$? and ?$R_n$?, while for the convex polytopes ?$R_n$?, ?$Q_n$? and ?$U_n$? a tight upper bound of the locating-dominating number is presented.
Keywords: konveksni politopi; lokacijsko-dominacijsko število